Iron-based mixed polyanion material as well as preparation method and application thereof
By preparing iron-based mixed polyanionic materials with quasi-single crystal structure and doping them with nickel elements, the problems of low electron conductivity and low sodium ion transport efficiency of iron-based polyanionic materials are solved, and the performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411501837.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
AI Technical Summary
Iron-based polyanionic materials have problems such as low inherent electron conductivity, accumulation of particle strain during charging and discharging, and low sodium ion transmission efficiency, which limits their development in the fields of fast charging and low-temperature reversible sodium storage.
By mixing sodium, iron, phosphorus, nickel and carbon sources, freeze-drying and sintering, iron-based mixed polyanionic materials with quasi-single crystal structures are prepared, and electron conductivity is improved by doping nickel elements and Sodium ion transport efficiency.
It significantly improves the inherent electronic conductivity and sodium ion transport efficiency of the material, improves the discharge specific capacity and cycling performance of the battery, and solves the problems of strain accumulation and slow sodium ion diffusion kinetics.
Smart Images

Figure CN119400824A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to an iron-based mixed polyanion material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have broad potential in large-scale energy storage due to their advantages such as high safety and low cost. Na4Fe3(PO4)2P2O7 (NFPP) is an iron-based polyanion material with high theoretical capacity (129mAh / g), low cost and suitable for operation at voltage platforms above 3.1V. However, it has defects such as low inherent electronic conductivity and sluggish sodium ion diffusion kinetics, which restrict the development of iron-based polyanion materials in the fields of fast charging and low-temperature reversible sodium storage.
[0003] Existing technologies to solve the above problems include doping with metal elements and carbon coating to improve the electronic conductivity of materials, reduce the direct contact between materials and electrolytes, thereby reducing side reactions and improving the electrochemical performance of materials. However, the above methods inevitably bring some adverse effects, such as uneven distribution of local elements, increased cost due to doping with precious metal elements, and reduced material capacity due to doping with inert elements. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art iron-based polyanion materials such as low inherent electronic conductivity, particle strain accumulation during charging and discharging, and low sodium ion transmission efficiency, thereby providing an iron-based mixed polyanion material and its preparation method and application.
[0005] To this end, the present invention provides the following technical solutions.
[0006] A method for preparing an iron-based mixed polyanion material comprises the following steps:
[0007] (1) mixing a sodium source, an iron source, a phosphorus source, a nickel source and a carbon source to prepare a mixture;
[0008] (2) freeze-drying the mixture and sintering it to obtain an iron-based mixed polyanion material.
[0009] In an optional embodiment, the molar ratio of the sodium source, iron source, phosphorus source, nickel source and carbon source is (0.05-0.25):(0.11-0.55):(0.2-1.0):(0.01-0.1):(0.01-0.05);
[0010] Preferably, the molar ratio of the nickel source to the carbon source is (0.04-0.08):(0.01-0.05);
[0011] Preferably, the ratio of the total molar amount of the iron source and the nickel source to the molar amount of the sodium source is (3-3.3):(2-4).
[0012] It should be noted that the sodium source and the phosphorus source can be from the same compound or different compounds, and the iron source and the phosphorus source can be from the same compound or different compounds. For example, when the raw material includes disodium hydrogen phosphate, it can provide both sodium and phosphorus; when the raw material includes iron phosphate, it can provide both iron and phosphorus.
[0013] In an optional embodiment, the sodium source includes at least one of disodium hydrogen phosphate, sodium carbonate, sodium oxalate, sodium bicarbonate and sodium dihydrogen carbonate;
[0014] In an optional embodiment, the iron source includes at least one of ferric phosphate, ferrous oxalate, ferric oxide and ferric nitrate;
[0015] In an optional embodiment, the phosphorus source includes at least one of disodium hydrogen phosphate and iron phosphate;
[0016] In an optional embodiment, the nickel source includes at least one of nickel nitrate, nickel sulfate and nickel oxide;
[0017] In an alternative embodiment, the carbon source includes at least one of citric acid and glucose.
[0018] In an optional embodiment, in step (1), a suitable amount of water is added to the mixture to dissolve and disperse the mixture;
[0019] In an optional embodiment, the step (1), the mixing further comprises a grinding step;
[0020] Preferably, the grinding speed is 1000-5000r / min;
[0021] Preferably, the grinding time is 1-5h.
[0022] In an optional embodiment, the freeze-drying is carried out at -10 to -100°C;
[0023] In an optional embodiment, the freeze drying is carried out at 10-100 Pa;
[0024] In an optional embodiment, the freeze-drying step further includes freezing at -10 to -50°C.
[0025] The freezing is to prevent excessive growth of ice crystals and aggregation of solid particles, so as to facilitate the subsequent freeze-drying step; the freezing is performed for 5-15 minutes, and then freeze-drying is performed.
[0026] In an optional embodiment, the sintering includes a first sintering and a second sintering;
[0027] Preferably, the heating rate of the first sintering is 1-5°C / min;
[0028] Preferably, the heating rate of the second sintering is 1-5°C / min.
[0029] In an optional embodiment, the sintering atmosphere includes at least one of argon and hydrogen.
[0030] In an optional embodiment, the temperature of the first sintering is 100-300°C;
[0031] In an optional embodiment, the first sintering time is 1-5h;
[0032] In an optional embodiment, the second sintering temperature is 500-650°C;
[0033] In an optional embodiment, the second sintering time is 11-13 hours.
[0034] The step of grinding is also included after the sintering is completed.
[0035] The invention also provides an iron-based mixed polyanion material prepared by the preparation method.
[0036] The present invention also provides an application of the iron-based mixed polyanion material prepared by the above preparation method in a sodium ion battery.
[0037] The technical solution of the present invention has the following advantages:
[0038] 1. The preparation method of the iron-based mixed polyanion material provided by the present invention comprises the following steps: (1) mixing a sodium source, an iron source, a phosphorus source, a nickel source and a carbon source to obtain a mixture; (2) freeze-drying and sintering the mixture to obtain an iron-based mixed polyanion material. The iron-based mixed polyanion material prepared by the present invention has a quasi-single crystal structure and good cycle performance. Specifically, the present invention reduces the strain accumulation of the iron-based polyanion material in the prior art during the cycle by designing a quasi-single crystal structure, thereby significantly improving the structural stability of the material in long-term cycles. Doping with nickel can replace part of the Fe in the iron-based polyanion material. 2+ , narrowing the band gap of iron-based polyanion materials to improve electronic conductivity, while Ni 2+ The ionic radius is larger than that of Fe 2+, the expanded lattice structure reduces the sodium ion diffusion barrier in the iron-based polyanion material and improves the sodium ion transmission efficiency; at the same time, the nickel element has the advantage of low cost compared to precious metal elements, and does not reduce the capacity of the material compared to inert elements. The present invention increases the interface area between the material and the electrolyte and shortens the ion diffusion path by doping with nickel elements and designing a quasi-single crystal structure, thereby improving the transmission rate and electronic transmission performance of the sodium ion battery. The iron-based mixed polyanion material prepared by the present invention has high inherent electronic conductivity, high discharge specific capacity after being made into a battery, and good cycle performance.
[0039] 2. The preparation method of the iron-based mixed polyanion material provided by the present invention, the prepared iron-based mixed polyanion material has a carbon coating layer, which can effectively improve the discharge specific capacity and cycle performance of the battery. Preferably, the molar ratio of the nickel source to the carbon source is (0.04-0.08): (0.01-0.05), and the addition amount of the nickel source in this range further improves the performance of the prepared iron-based mixed polyanion material, and the prepared battery has a higher discharge specific capacity and better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 is a SEM electron microscope image of the iron-based mixed polyanion material prepared in Example 1 of the present invention;
[0042] Figure 2 It is a SEM electron microscope image of the iron-based polyanion material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0044] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0045] Example 1
[0046] This embodiment provides a method for preparing an iron-based mixed polyanion material, comprising the following steps:
[0047] (1) 0.2 mol of Na2HPO4·2H2O, 0.2 mol of FePO4, 0.04 mol of FeC2O4·2H2O, 0.06 mol of Ni(NO3)2·6H2O and 0.02 mol of citric acid were dissolved in 500 mL of water and stirred. The mixture was ground at 3000 r / min for 3 h to obtain a suspension.
[0048] (2) Freezing the suspension at -40°C for 10 min, and freeze-drying it at -70°C and a vacuum degree of 50 Pa, wherein the freeze-dried product is dry and loose; in a mixed atmosphere of argon and hydrogen (the volume ratio of argon and hydrogen is 92:8), heating the suspension to 300°C at a heating rate of 2°C / min and sintering the suspension for 3 h, and then heating the suspension to 550°C at a heating rate of 2°C / min and sintering the suspension for 12 h, and grinding the suspension through a 400-mesh sieve in an agate mortar to obtain an iron-based mixed polyanion material.
[0049] The SEM electron microscope image of the prepared iron-based mixed polyanion material is as follows: Figure 1 As shown, the SEM image shows that the polyanion material prepared in this embodiment has a quasi-single crystal structure.
[0050] Example 2
[0051] This embodiment provides a method for preparing an iron-based mixed polyanion material. Compared with Example 1, the only difference is that in step (1), 0.07 mol of FeC2O4·2H2O and 0.03 mol of Ni(NO3)2·6H2O are added instead of 0.04 mol of FeC2O4·2H2O and 0.06 mol of Ni(NO3)2·6H2O in Example 1.
[0052] Example 3
[0053] This embodiment provides a method for preparing an iron-based mixed polyanion material. Compared with Example 1, the only difference is that in step (1), 0.01 mol of FeC2O4·2H2O and 0.09 mol of Ni(NO3)2·6H2O are added instead of 0.04 mol of FeC2O4·2H2O and 0.06 mol of Ni(NO3)2·6H2O in Example 1.
[0054] Example 4
[0055] This embodiment provides a method for preparing an iron-based mixed polyanion material, comprising the following steps:
[0056] (1) 0.25 mol of Na2HPO4·2H2O, 0.25 mol of FePO4, 0.02 mol of FeC2O4·2H2O, 0.06 mol of Ni(NO3)2·6H2O and 0.05 mol of citric acid were dissolved in 1000 mL of water, stirred, and the mixture was ground at 5000 r / min for 5 h to obtain a suspension.
[0057] (2) Freezing the suspension at -10°C for 10 min, freeze-drying at -20°C and a vacuum degree of 100 Pa, wherein the freeze-dried product is dry and loose; heating to 280°C at a heating rate of 5°C / min and sintering for 5 h in a mixed atmosphere of argon and hydrogen (the volume ratio of argon to hydrogen is 92:8), then heating to 630°C at a heating rate of 5°C / min and sintering for 12 h, and grinding the suspension through a 400-mesh sieve in an agate mortar to obtain an iron-based mixed polyanion material.
[0058] Comparative Example 1
[0059] This comparative example provides a method for preparing an iron-based polyanion material. Compared with Example 1, the only difference is that step (2) is different.
[0060] The step (2) comprises: spray drying the suspension at an outlet temperature of 120° C., heating the suspension to 300° C. at a heating rate of 2° C. / min and sintering the suspension for 3 h in a mixed atmosphere of argon and hydrogen (the volume ratio of argon and hydrogen is 95:5), then heating the suspension to 550° C. at a heating rate of 2° C. / min and sintering the suspension for 12 h, and grinding the suspension through a 400-mesh sieve in an agate mortar to obtain an iron-based polyanion material.
[0061] The SEM electron microscope image of the prepared iron-based polyanion material is as follows: Figure 2 shown.
[0062] Comparative Example 2
[0063] This comparative example provides a method for preparing an iron-based polyanion material. Compared with Example 1, the only difference is that in step (1), 0.06 mol of Ni(NO3)2·6H2O is not added.
[0064] Test Case
[0065] The performance tests of the iron-based polyanion materials obtained in the above examples and comparative examples are as follows:
[0066] The iron-based polyanion material, acetylene carbon black and PVDF were evenly mixed in a mass ratio of 80:12:8, 1-methyl-2-pyrrolidone was added and ball-milled for 1 hour to obtain the positive electrode slurry, which was evenly coated on an aluminum sheet, dried, and pressed into a positive electrode sheet; in an argon atmosphere in a glove box, a CR2032 button battery was assembled with a metal lithium sheet as the counter electrode, glass fiber as the diaphragm, and 1 mol / L NaClO4 PC solution as the electrolyte.
[0067] The performance test of the blue-electric test system for the battery prepared above is carried out as follows:
[0068] (1) 0.1C discharge specific capacity test method: At room temperature, within the cut-off voltage range of 2.0V-4.0V, the battery is charged at 0.1C and discharged once at 0.1C. The results are shown in Table 1.
[0069] (2) Cycle performance test method: At room temperature, within the cut-off voltage range of 2.0V-4.0V, the battery was charged at 1C and discharged at 1C for 50 cycles. The results are shown in Table 1. The cycle performance calculation formula is as follows:
[0070] Cycle performance = 100% × 50th discharge capacity / 1st discharge capacity
[0071] Table 1 Performance results of various embodiments and comparative examples
[0072] Discharge specific capacity (mAh / g) Cycle performance (%) Example 1 109.8 98.1 Example 2 100.3 93.0 Example 3 94.1 90.2 Example 4 97.8 91.4 Comparative Example 1 90.5 75.6 Comparative Example 2 90.1 88.4
[0073] It can be seen from Table 1 that the iron-based mixed polyanion material prepared in the present invention has high discharge specific capacity and good cycle performance.
[0074] By comparing Example 1 with Comparative Example 1, the prepared iron-based mixed polyanion material has a quasi-single crystal structure, a high discharge specific capacity, and greatly improved cycle performance. Compared with Comparative Example 1 of the non-single crystal material prepared by spray drying, the quasi-single crystal structure material prepared by freeze drying in the present invention has a higher discharge specific capacity and better cycle performance, indicating that the iron-based mixed polyanion material prepared by the preparation method of the present invention is more excellent.
[0075] By comparison between Example 1 and Comparative Example 2, the discharge specific capacity and cycle performance of the iron-based polyanion material obtained without adding nickel element doping are significantly reduced, indicating that doping nickel element in the present invention can improve the discharge specific capacity and cycle performance of the material. Furthermore, by comparison between Example 1 and Examples 2-3, the molar ratio of the nickel source to the carbon source is preferably (0.04-0.08): (0.01-0.05). The iron-based mixed polyanion material obtained within this range has a higher discharge specific capacity and better cycle performance.
[0076] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing an iron-based mixed polyanion material, characterized in that: The steps include: (1) mixing a sodium source, an iron source, a phosphorus source, a nickel source and a carbon source to prepare a mixture; (2) freeze-drying the mixture and sintering it to obtain an iron-based mixed polyanion material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the sodium source, iron source, phosphorus source, nickel source and carbon source is (0.05-0.25):(0.11-0.55):(0.2-1.0):(0.01-0.1):(0.01-0.05); Preferably, the molar ratio of the nickel source to the carbon source is (0.04-0.08):(0.01-0.05); Preferably, the ratio of the total molar amount of the iron source and the nickel source to the molar amount of the sodium source is (3-3.3):(2-4).
3. The preparation method according to claim 1 or 2, characterized in that: The sodium source comprises at least one of disodium hydrogen phosphate, sodium carbonate, sodium oxalate, sodium bicarbonate and sodium dihydrogen carbonate; and / or, The iron source comprises at least one of ferric phosphate, ferrous oxalate, ferric oxide and ferric nitrate; and / or, The phosphorus source includes at least one of disodium hydrogen phosphate and iron phosphate; and / or, The nickel source comprises at least one of nickel nitrate, nickel sulfate and nickel oxide; and / or, The carbon source includes at least one of citric acid and glucose.
4. The preparation method according to claim 1, characterized in that: In the step (1), the mixing further comprises a grinding step; Preferably, the grinding speed is 1000-5000r / min; Preferably, the grinding time is 1-5h.
5. The preparation method according to claim 1, characterized in that: The freeze drying is carried out at -10 to -100°C and / or 10 to 100 Pa; and / or, The freeze drying step also includes freezing at -10 to -50°C.
6. The preparation method according to claim 1, characterized in that: The sintering includes a first sintering and a second sintering; Preferably, the heating rate of the first sintering is 1-5°C / min; Preferably, the heating rate of the second sintering is 1-5°C / min.
7. The preparation method according to claim 6, characterized in that: The sintering atmosphere includes at least one of argon and hydrogen.
8. The preparation method according to claim 6 or 7, characterized in that: The first sintering temperature is 100-300° C.; and / or, The first sintering time is 1-5h; and / or, The second sintering temperature is 500-650° C.; and / or, The second sintering time is 11-13 hours.
9. The iron-based mixed polyanion material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the iron-based mixed polyanion material prepared according to the preparation method according to any one of claims 1 to 8 in sodium ion batteries.